Numerical study of propane-air mixture combustion in a burner element - Carlos Tavares Pinho (2008)
This study considers numerical simulations of the combustion of propane with air, in a burner element due to high temperature and velocity gradients in the combustion chamber. The effects of equivalence ratio (Φ) and oxygen percentage (γ) in the combustion air are investigated for different values of Φ between 0.5 and 1.0 and γ between 10 and 30%. In each case, combustion is simulated for the fuel mass flow rate resulting in the same heat transfer rate (Q) to the combustion chamber. Numerical calculations are performed individually for all cases with the use of the Fluent CFD code. The results shown that the increase of equivalence ratio corresponds to a significantly decrease in the maximum reaction rates and the maximum temperature increase with the increases of oxygen percentage. Mixing hydrogen with propane causes considerable reduction in temperature levels and a consequent reduction of CO emissions.